Public Policies and the Employment Dynamics among new Mothers - A Comparison of Finland, Norway and Sweden - Marit Rønsen; Marianne Sundström (Statistics Norway, Research Department, 1999)
This paper compares the employment patterns of women after first and second birth in Finland, Norway and Sweden during 1972-92, focusing on the impact of parental leave and childcare programs on the transitions to full-time and part-time work. The results unanimously point to the great importance of the programs. Women who are entitled to a paid leave resume employment faster than non-eligible women. As leave periods are prolonged the difference between the two groups diminishes but still prevails in the end of the study period. The higher entry risks for entitled mothers remain after controlling for own wage and spouse's income.
Keywords: J22; J13; 330; Female labor supply; maternity/parental leave; childcare; childbirth; hazard rate model